Getting Special Care Dentistry Ready for a Foreseeable Future. Reinstated Services and Mitigation Measures to Curb COVID-19 Disruption - Arkadiusz Dziedzic (MDPI AG, 2021)
In March 2020, dental care providers, including special care dentistry (SCD) services, had to face an extraordinary change of their standard operating procedures (SOP), with deferred domiciliary dental care, withholding conscious dental sedation services and disrupted routine care [...]